1999
DOI: 10.3141/1660-05
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Annual Average Daily Traffic for Nonstate Roads in a Florida County

Abstract: A study was undertaken to develop a methodology to estimate annual average daily traffic (AADT) for nonstate roads in urbanized areas in Florida. The current practice related to the estimation of AADT for nonstate roads has been of great concern to the Florida Department of Transportation because of the potential lack of accuracy in the estimated data. For this study, a multiple regression model was developed for estimating AADT on nonstate roads. The model utilized a large sample size (data from 450 count sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
1
19
0
Order By: Relevance
“…Cheng [4] proposed a regression model based on road functional classification -road width, surface type and population in geographical areas to estimate traffic flow. Xia et al [32] studied a model to estimate AADT for non-state roads in urbanized areas in Florida, which involved both road geometry (e.g. the number of lanes, road functional classification) and socioeconomic variables (e.g.…”
Section: Review Of Researches On Traffic Flowmentioning
confidence: 99%
“…Cheng [4] proposed a regression model based on road functional classification -road width, surface type and population in geographical areas to estimate traffic flow. Xia et al [32] studied a model to estimate AADT for non-state roads in urbanized areas in Florida, which involved both road geometry (e.g. the number of lanes, road functional classification) and socioeconomic variables (e.g.…”
Section: Review Of Researches On Traffic Flowmentioning
confidence: 99%
“…For example, Mohamad et al [12] estimated this model for estimation of AADT for county roads using population, highway mileage, income, and the presence of interstate highways. Xia et al [13] developed a multiple regression model for AADT of non‐state roads in Florida using roadway characteristics, socio‐economic variables. Later, Zhao and Park [14] recognised the importance of spatial effects and used geographically weighted regression models to estimate AADT or truck AADT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Mohammad et al incorporated relevant demographic variables for county roads into a traffic prediction model in [16]. Xia et al [29] found roadway characteristics, such as the number of lanes, functional classification, and area type, which are contributing predictors to the AADT estimation of nonstate roads in urbanized areas in Florida, USA. Zhao and Chung [32] developed and compared four multiple linear regression models using geographic information system (GIS) technology.…”
Section: Introductionmentioning
confidence: 99%